Can Automatic Tax Increases Pay for the Public Spending Effects of Population Ageing in New Zealand? - John Creedy; Norman Gemmell (New Zealand Government, The Treasury, 2013)
This paper examines the extent to which projected aggregate tax revenue changes, in association with population ageing over the next 50 years, can be expected to finance expected increases in social welfare expenditures. It uses projections from two separate models, dealing with social expenditures and income tax and GST revenue. The results suggest that the modest increase required in the overall average tax rate over the next 50 years can be achieved automatically by adjusting income tax thresholds using an index of prices rather than wages. Based on evidence about the New Zealand tax system over the last 50 years, comparisons of average and marginal tax rates suggest that such an increase may be feasible and affordable. The paper discusses the range of considerations involved in deciding if this automatic increase in the aggregate average tax rate, via real fiscal drag of personal income taxes, is desirable compared with alternative fiscal policy changes.
Keywords: E62; H68; 330; Social welfare expenditures; income tax; GST; real fiscal drag; ageing population